Hardly a gentleman - James, Eloisa (James, Eloisa. Accidental brides novel, 2025)
"Desperate after her Season comes to a spectacularly disastrous end, the Honorable Miss Clara Vetry jumps into a carriage hired to take a housekeeper to Scotland. The laird of Castle CaerLaven has no interest in a wife, especially a love match--but when Caelan sees his new housekeeper, he changes his mind. Marriage to a delectable bookworm strikes him as a perfect arrangement. To his surprise, Clara refuses his proposal once . . . and again . . . yet again. When her true identity is revealed, and they're forced to marry, Caelan realizes he has a far more crucial challenge. He finally has Clara's hand--but how will he ever win her heart?" --